Participation à la conférence de l’ACFAS sur les femmes officielles des communautés linguistiques minoritaires à Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Caractéristiques sociodémographiques des minorités visibles - Reste du Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques pour la province de Québec et ses régions RTS.

Socio-Demographic Profile of Québec's English-speaking Youth Aged 15-29 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This report profiles the situation of English-speaking citizens of Québec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood. Youth is a stage of life characterized by challenges that can be decisive in the quality of life of individuals and their communities and for most Québecers aged 15-29, these milestones are: completing school, gaining occupational experience and even starting a family and establishing a household. This report offers current information organized to support “the village” - from policymakers and program managers to public institutions, community organizations and networks - whose actions impact the lives of minority language youth striving to build their future and the future of all Québec’s citizens.

Caractéristiques sociodémographiques des minorités visibles au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques pour la province de Québec et ses régions RTS.

Socio-Demographic Characteristics of Visible Minorities in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec.

Socio-Demographic Characteristics of Visible Minorities in Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for the rest of Québec.

Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Employment Situation of English Speakers in Québec - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Propositions prébudgétaire 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
La Table ronde provinciale de l'emploi (PERT) a le plaisir de soumettre ce mémoire et proposition aux consultations prébudgétaires 2024-25 du ministère des Finances. Fondée en 2020, PERT est une organisation à but non lucratif qui se consacre aux problèmes d'emploi et d'employabilité auxquels sont confrontées les communautés d’expression anglaise du Québec. Depuis sa création, PERT est devenu le principal porte-parole des solutions aux problèmes d'emploi des Québécois d’expression anglaise. Grâce à son travail de recherche et de coordination des parties prenantes, PERT a publié plus de 25 rapports qui décrivent les problèmes et les besoins des Québécois d’expression anglaise en matière d'emploi dans les 17 régions de la province. PERT compte parmi ses plus de 90 membres des prestataires de services d'emploi, des établissements d'enseignement, et des organisations régionales et employeurs. La situation d'emploi de la population d’expression anglaise du Québec continue de se détériorer, comme en témoignent les taux de chômage plus élevés et les obstacles liés à la langue française auxquels les Québécois d’expression anglaise sont confrontés sur le marché du travail québécois. Dans ce mémoire, nous identifions deux facteurs clés qui contribuent aux défis continus des Québécois d’expression anglaise en matière d'emploi : le manque de services et de programmes d'emploi ciblés pour les Québécois d’expression anglaise et le manque de programmes de formation en français intégrés au travail pour les aider à entrer sur le marché du travail et à y rester. Les difficultés économiques et d'emploi des Québécois d’expression anglaise s'inscrivent dans le contexte plus large des vents contraires auxquels le Québec est confronté, notamment les pénuries de main-d'oeuvre sans précédent, le déclin démographique et les problèmes liés à l'attraction et à la rétention des talents. Ce mémoire résume les résultats de la recherche de PERT, en particulier les défis en matière d'emploi auxquels est confrontée la communauté d’expression anglaise du Québec, et propose des recommandations pour le prochain budget qui permettront de relever ces défis et de créer un Québec plus productif, plus inclusif et plus prospère pour tous.

Situation d’emploi des personnes d'expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2024)

Exploring the English-speaking Landscape : A Typology of Vulnerability Associated with Employment in Quebec's English-speaking Population - Warnke, Jan; Bolger, Laura-Lee (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
This exploratory study uses geodemographic analytical methods to investigate the English-speaking population of Quebec, with a specific focus on vulnerability indicators associated with employment and their spatial distribution within the province. Using Ward’s cluster analysis method, eight distinct groups were identified and mapped, each showcasing unique characteristics that warrant tailored policy measures to effectively tackle regional employment challenges. Future research should delve into the differential impacts of various variables across clusters, particularly those related to mobility and aboriginal identity, thereby facilitating the derivation of targeted policy interventions.

Socio-demographic Profile of the Population Aged 55 and Over : Province of Quebec - Pocock, Joanne (2023)

Press Release: New study reveals economic precarity and limit job supports for racialized communities and English-speaking immigrants in Québec. - Provincial Employment Roundtable (PERT) (2023)

Une nouvelle étude révèle la précarité économique et l’insuffisance des aides à l’emploi pour les communautés racialisées et les immigrants d’expression anglaise au Québec - Provincial Employment Roundtable (PERT) (2023)

Economic Development and Community Vitality : A Report on Federal Funding Streams Available to the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN); Community Economic Development and Employability Corporation (CEDEC); Youth Employment Services (YES) (2023)
The following report provides an overview of the main federal funding streams for the English-speaking community in Quebec (ESCQ) along with the French-speaking community in the rest of Canada. This includes an overview and analysis of the Canada Economic Development for Quebec Regions (CED-Q), including the Official Languages Economic Development Initiative (EDI) and other official language minority communities (OLMCs) specific funding streams: Regional Economic Growth through Innovation (REGI), the Quebec Economic Development Program (QEDP), and the Community Futures Program (CFP). As a means of comparing funding levels for the French-speaking community outside of Quebec, this study also reviews Canada Economic Development for the Rest of Canada (CED-ROC).
Keywords: Official Language Minority Community (OLMC)

Mapping Employment Supports for Québec's Racialized and Immigrant English-speaking Communities - Gagnon, Morgan; Kuzviwanza, Sta (Provincial Employment Roundtable (PERT), 2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 10

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 11

Provincial Employment Roundtable : Québec and the rest: A survey of national and international approaches to adult language training - Kuzviwanza, Sithandazile; Holt, Cimminnee (Provincial Employment Roundtable (PERT), 2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 9

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 10

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 12

Le magazine en ligne de la CEDEC : De meilleures économies pour de meilleures vies - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 13

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 6

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 7

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 5

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2023)
Number of pages: 6

Demographic Profiles of Québec's English-speaking Communities, Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2021-2022 - Provincial Employment Roundtable (PERT) (2023)

Annual Report 2022-2023 - Provincial Employment Roundtable (PERT) (2023)

Mémoire : Réflexion sur l'avenir de la langue française - Provincial Employment Roundtable (PERT) (2023)

Strategic Plan 2024-2027 : The Way Forward - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is a non-profit multi-stakeholder initiative focused on addressing the employment and employability challenges facing Québec’s English-speaking community. This strategic plan for 2024-2027 outlines five key shifts, the introduction of a third organisational pillar, and eleven strategic goals that will guide PERT’s efforts to address the unique employment challenges faced by English speakers in Québec.

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 4

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 4

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 13

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 15

Enquête de 2021 sur l’emploi auprès des Québécois(es) et des organisations d’expression anglaise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport expose les expériences des Québécois·e·s d’expression anglaise dans la province au regard de l’emploi ainsi que les différents enjeux rencontrés et les besoins éprouvés par cette population sur le marché du travail. Désignée « communauté linguistique minoritaire officielle » du Québec, la population québécoise d’expression anglaise est toutefois caractérisée par une réelle diversité identitaire, comportant ainsi une pluralité de sous-communautés qui ne connaissent pas toutes les mêmes défis. Des points de convergence néanmoins existent, notamment du point de vue du statut socioéconomique de la communauté d’expression anglaise prise dans son ensemble. De fait, en dépit du statut d’élite socioéconomique qu’occupaient historiquement les personnes d’expression anglaise au Québec, la communauté actuelle est dans son ensemble caractérisée, en comparaison d’avec la majorité linguistique d’expression française, par des taux élevés de chômage et de plus faibles revenus. Ce rapport s’appuie des données provenant d’une enquête réalisée en deux volets. Le premier volet consistait à sonder 259 Québécois·e·s d’expression anglaise à propos de leur relation au marché du travail, de leur niveau de français, des répercussions de la pandémie et des obstacles à leur accès au marché du travail. À cette première enquête venait s’ajouter une seconde s’intéressant aux points de vue de 29 organisations qui emploient des personnes d’expression anglaise et servent leurs intérêts, quant au paysage de l’emploi pour cette population, et aux effets sur l’emploi des politiques linguistiques promouvant le français.

Le magazine en ligne de la CEDEC : Chef de file reconnu de la collaboration innovatrice entre les secteurs public et privé et la société civile - Community Economic Development and Employability Corporation (CEDEC) (2022)
Number of pages: 9

L'étude éducation à l'emplois (E2E) - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
Au Québec, la communauté noire et la communauté d'expression anglaise occupent toutes deux des positions relativement précaires sur le plan économique et de l'emploi : toutes deux connaissent des taux de chômage supérieurs à la moyenne et gagnent des revenus médians après impôt inférieurs à ceux de la population totale de la province. La communauté noire d'expression anglaise (CNEA) se trouve à l'intersection de ces deux communautés et subit la double marginalisation d'être à la fois une minorité raciale et linguistique au Québec.

The Education to Employability Study - Black Community Resource Centre (BCRC); Provincial Employment Roundtable of Quebec (2022)
In Québec, both the Black community and the English-speaking community occupy relatively precarious economic and employment positions: both experience higher-thanaverage unemployment rates and earn lower median after-tax incomes compared to the province’s total population. The English-speaking Black Community (ESBC) sits at the intersection of these two communities, and experiences the double marginalization of being both a racial and linguistic minority in Québec.

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

French-Language Training for the Workforce : A review of French-language training programs for the workforce in Québec - Provincial Employment Roundtable (PERT) (2022)
This report examines the status of French-language workforce programs (FLWPs) in Québec. FLWPs consist of language learning that is specifically designed to increase the integration of workers into the labour market by focusing on the vocabulary and language skills they need to improve their employability. In this report, we conducted an inventory of FLWPs that are available to French-language learners and identified the key needs, gaps and areas for improvement in the ecosystem.

Programmes de francisation de la main-d'oeuvre au Québec : Évaluation des programmes de francisation de la main-d'oeuvre québécoise - Provincial Employment Roundtable (PERT) (2022)
Le présent rapport se penche sur l’état des programmes de francisation pour la main-d’oeuvre (PFMO) au Québec. Les PFMO sont des cours de français spécifiquement conçus pour accroître l’intégration des apprenantes et apprenants de langues sur le marché du travail en étant axés sur le vocabulaire et les compétences linguistiques qui contribuent à leur employabilité. Dans ce rapport nous avons recensé les PFMO offerts aux apprenantes et apprenants de langue française, et relevé les besoins clés, les lacunes et les possibilités d’amélioration au sein de l’écosystème.

Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2022)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

Québec - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Black in Quebec - Davids, John; Fang, Xiaoyan; Bramble, Shania (2021)

2nd Annual General Meeting 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report 2020-2021 - Regional Development Network (RDN) (2021)

East Island Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Annual Report 2020-2021 - Youth Employment Services (YES) (2021)
As a not-for-profit organization, YES enriches the community by providing English-language support services to help Quebecers find employment and start and grow businesses. YES Employment + Entrepreneurship has been broadening access to opportunities for Quebec’s English-speaking community for over 25 years now. As we reflect on the organization’s 25th anniversary in the midst of the pandemic, we are reminded of the vital importance of our career and business support services.

Rapport annuel 2020-2021 - Youth Employment Services (YES) (2021)
En qualité d’organisme sans but lucratif, YES contribue à l’enrichissement de la communauté en offrant des services de soutien en anglais pour aider les québécois à trouver un emploi ou démarrer ou développer leurs entreprises. Depuis plus de 25 ans, YES Emploi + Entrepreneuriat facilite l’accès à différentes opportunités de croissance auprès de la communauté d’expression anglaise du Québec. Célébrer le 25e anniversaire de notre organisation en pleine pandémie nous rappelle à quel point nos services d’accompagnement à l’emploi et d’aide aux entreprises sont d’une importance vitale.

Black in Quebec : Progress Report - Davids, John; Fang, Xiaoyan (2020)

Black-White Differences in Canadian Educational Attainments and Earnings - Masella, Rosalie; McIntosh, James (2019)
Data from two large Canadian surveys are used to analyze educational and earnings performance of Blacks and Whites. The main purpose of this study is to determine how well blacks perform relative to Whites in these two areas.

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Parallel title: QUESCREN Working Paper no.1
Keywords: Official Language Minority Community (OLMC)

Les Québécois d'expression anglaise et la fonction publique du Québec - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
Ce document de travail fournit des renseignements contextuels sur la participation des anglophones à la fonction publique du Québec (FPQ). La première partie fait la synthèse de l’information pertinente recueillie auprès de sources primaires et secondaires. La seconde offre un résumé de nos discussions exploratoires avec des personnes-ressources clés, suivi de nos observations.
Parallel title: Document de travail QUESCREN no.1
Keywords: Official Language Minority Community (OLMC)

Promoting Opportunities for Youth Community Partnerships : A Policy Brief - Lai, Edward; Winrow, Adrienne; Orme, Charlie (Youth for Youth Québec (Y4Y Québec), 2019)
Across Canada, youth retention and success have always been key in ensuring the continued vitality of official language minority communities (OLMCs). Within the context of Quebec, retention in particular is a constant challenge, where English-speaking youth are disproportionately apt to pursue professional opportunities outside of the province. While this option should never be condemned, it is nonetheless important to ensure that those who wish to remain have access to the resources necessary to help them thrive therein. With this in mind, and considering that youth retention is equally beneficial to the state, policymakers need to be in a position to support organizations that are working towards this objective.
Keywords: Official Language Minority Community (OLMC)

Careers in Mental Health - Assistance and Referral Centre (ARC) (2019)

Careers in Nursing - Assistance and Referral Centre (ARC) (2019)

Technical Medical Careers - Assistance and Referral Centre (ARC) (2019)

Therapy & Rehabilitation Careers - Assistance and Referral Centre (ARC) (2019)

English-speaking Blacks in Quebec : Highlights from the 2016 Census - Floch, William (2018)

Noirs d’expression anglaise au Québec : faits saillants du recensement de 2016 - Floch, William (2018)

Youth Internships in Community Media : A First Step Towards Capacity Building for Official Language Community Media in Minority Setting - Consortium of Official Language Minority Community Media (2018)
Keywords: Official Language Minority Community (OLMC)

Participation of English-speaking Canadians in the Federal Civil Service in Quebec (outside of the National Capital Region) - Quebec Community Groups Network (QCGN) (2018)

Retention Program : Monitoring of Internship Students - Storr, Caroline; Hendrickson, Mary (2018)

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

Building a Career as an Artist - Macdonald, Amy; Shaughnessy, Kyra (2015)

ACCORD Sample Contract - English Language Arts Network (ELAN) (2012)

A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)

Special Needs Project - Lavallée, Marissa (2007)

Self-Employment and Employment in Quebec's English-speaking Cultural Communities and Visible Minorities : Prospects and Problems - Jedwab, Jack (Youth Employment Services (YES), 2006)
What are the principal barriers to self-employment and employment for members of Quebec’s English-speaking visible minorities and cultural communities? The question is considered in this report in view of the ongoing challenges that some members of English-speaking visible minorities and cultural communities face in the current economy. The specific aim is to improve our understanding of factors which prevent members of Quebec’s English-speaking visible minorities and cultural communities from achieving self-employment and employment goals.

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Alliance Quebec Presents Equity Brief to Quebec National Assembly - Alliance Quebec (AQ) (2000)

Brief on Draft Law Number 143 Equity in the Civil Service - Alliance Quebec (AQ) (2000)
As the Committee studying draft law 143 is aware, Alliance Quebec is an association which lobbies governments at all levels for the rights and needs of the Englishspeaking population of Quebec to be respected. Our organization has chapters in Montreal, West Island, East Island, South Shore, Laval, Rouyn-Noranda, Val d'Or, Saguenay Lac Saint Jean, Mauricie and the Upper and Lower Laurentians. We also have our provincial youth commission that represents young people province-wide. In all, over 83 percent of Quebec's English-speaking population resides in Alliance Quebec territory.

Conference on Job Equity and Employability - Johnson, William (2000)

A Brief on Quebec's English-speaking Youth on the Occasion of the Youth Summit - Alliance Quebec (AQ) (2000)
We, the English-speaking youth of Quebec, come before you today to ask that our distinctive voices be heard. We share many of the concerns, problems and preoccupations of our French-speaking brothers and sisters. But we have anguishes, specific and poignant, which are ours alone, and which you will not hear about from the other participants and observers at the Youth Conference.

Alliance Quebec Youth Seek Meeting with Premier - Alliance Quebec (AQ) (1999)

Transfer of Manpower Could Sacrifice Essential Protections for Minority-Language Services and Information : AQ - Alliance Quebec (AQ) (1997)

Alliance Quebec Brief to the Standing Committee on Cultural Communities & Immigration on the Charter of the French Language - Alliance Quebec (AQ) (1983)
More than a year and a half dgo, the Premier of this province publically called for a dialogue on Bill 101. He stated the hope that the dialogue would be fruitful, and that it would be marked by reasonableness and good faith on the part of everyone concerned. Alliance Quebec, which from the beginning of its existence has proven its commitment to reasonab'l eness and good faith, remains convinced that Quebecers can attain a fair, meaningful and pr oductive resolution of the language debate. This is a debate which has continued for too long, consuming or diverting energy, provoking friction and causing in human terms, considerable damage and loss. We can Iive together, French-speaking and Enlish-speaking Quebecers, in dignity, security and mutual respect; the obstacles are not insurmountable and it is time that they were removed.

A Policy for the English-speaking Community of Quebec - Alliance Quebec (AQ) (1982)
We are almost one million English-speaking Quebecers. We regard Quebec as our home. Our community has participated in more than two hundred years of Quebec's history. We have contributed to the building of one of the world's most stable, prosperous and culturally rich societies. We believe that the interplay of the influences of Quebec's French-speaking and English-speaking peoples has been mutually enriching.

Brief on Teacher Classification Presented by Quebec Federation of Home & School Associations to Commission of Study on the Classification of Teachers - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations at its Annual General Meeting held in May 1971, passed two resolutions on the issue and conflict arising in respect of Teacher Classification to be directed to the Minister of Education.

CEDEC Brand Handbook - Community Economic Development and Employability Corporation (CEDEC)

Manuel de la marque de commerce de la CEDEC - Community Economic Development and Employability Corporation (CEDEC)

The Black Community Resource Centre and the Provincial Employment Rountable Present : The Education to Employability Webinar - Davids, John; Fang, Xiaoyan; Gagnon, Morgan

The Vision of the Social and Solidarity Economy Entrepreneurial Network (SEE Net) - Regional Development Network (RDN)

Provincial Employment Roundtable - Salter, Nicholas

Best Hiring Practices - Youth Employment Services (YES)

Employee Contract & Handbook - Youth Employment Services (YES)

Regional Resources for Employment - Youth Employment Services (YES)

Setting Up an Employee File - Youth Employment Services (YES)